Translating Policies into Informal Settlements' Critical Services: Reframing, Anchoring and Muddling Through. (December 2016) - Kain, Jaan‐Henrik; Nyakinya, Belinda; Odhiambo, Nicholas; Oloko, Michael; Omolo, John; Otieno, Silas; Zapata, Patrik; Zapata Campos, María José
Summary: This paper examines how policies and plans are translated into informal settlements' practice. It builds on literature on policy implementation practice and organization studies, and more particularly, it applies the concepts of reframing, anchoring and muddling through. The paper is informed by the case of Kisumu City in Kenya and its Kisumu Integrated Solid Waste Management Plan and its implementation on Kisumu's informal settlements. The plan was funded by the Swedish International Development Agency through the United Nations Human Settlement Programme and implemented from 2007 to 2009. The study is based on action research carried out by a multidisciplinary and transdisciplinary group of researchers, through focus groups, participatory workshops, collaborative action, in‐depth interviews, document analysis and observations. The paper examines what original aspects of Kisumu Integrated Solid Waste Management Plan were translated, that is, which ones faded out and which ones became stabilized into and travel as 'best practices' to other locations. The paper shows how the generation of 'best practices' can be loosely coupled with the practices that policy seeks to change. It concludes, in line with previous research in the field, how successful policy implementation is based on cultural and political interpretations rather on evidence of improved practices. Copyright © 2016 John Wiley & Sons, Ltd.